2017
DOI: 10.1039/c7gc01432e
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygenates and effect of operating conditions in the deactivation of a Ni supported catalyst during the steam reforming of bio-oil

Abstract: This work investigates the correlation of the reaction conditions and the reaction medium composition with the deactivation behavior of a Ni/La2O3-αAl2O3 catalyst used in the steam reforming of bio-oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 70 publications
3
84
0
Order By: Relevance
“…The results in Section 2.3 prove that the total removal of coke is not enough for the recovery of the activity of the Ni catalysts used in the OSR of raw bio-oil, which should be attributed to the existence of other deactivation causes besides coke deposition, such as metal sintering or changes in the metal species. The sintering of Ni at 700 • C has been previously reported for Ni/LaAl catalyst used in the SR of bio-oil [15,61] for the commercial G90 catalysts used in the SR of biomass pyrolysis volatiles [73] and for spinel NiAl 2 O 4 catalysts prepared by different methods and used in the OSR of bio-oil [66]. Besides the changes in the metallic structure originated in the reaction step, the effect of the operating conditions in the regeneration step upon the physical-chemical properties of the catalyst (especially the metal properties) should be also considered, as they would be responsible for the activity of the regenerated catalyst.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results in Section 2.3 prove that the total removal of coke is not enough for the recovery of the activity of the Ni catalysts used in the OSR of raw bio-oil, which should be attributed to the existence of other deactivation causes besides coke deposition, such as metal sintering or changes in the metal species. The sintering of Ni at 700 • C has been previously reported for Ni/LaAl catalyst used in the SR of bio-oil [15,61] for the commercial G90 catalysts used in the SR of biomass pyrolysis volatiles [73] and for spinel NiAl 2 O 4 catalysts prepared by different methods and used in the OSR of bio-oil [66]. Besides the changes in the metallic structure originated in the reaction step, the effect of the operating conditions in the regeneration step upon the physical-chemical properties of the catalyst (especially the metal properties) should be also considered, as they would be responsible for the activity of the regenerated catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the existence of an additional deactivation cause, besides coke deposition, such as Ni sintering due to the high temperature and water content in the reaction medium [61,66]; on the other hand, there could be metal loss due to the detachment during coke combustion of some Ni 0 particles located at the edges of the coke filaments. Consequently, the regeneration treatment should be able not only to remove coke but also to re-disperse the Ni particles, and moreover, the loss of Ni during the regeneration should be avoided.…”
Section: Regenerability Of the Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature programmed oxidation (TPO) using thermogravimetric analysis (TGA or TG) is by far the most common method used for the characterization of coke deposited on catalysts, gaining insights into the amount, nature or location of coke . The standard experimental procedure involves a linear heating program, and it allows a coke characterization based on the general criterion that fractions burning at lower temperatures have: (i) more hydrogenated nature, higher proportion of aliphatics with respect to aromatics; (ii) more oxygenated nature; (iii) higher accessibility within the catalyst porous structure; and/or (iv) higher proximity of coke to metallic sites, which catalyze coke combustion . TG‐TPO also allows the determination of coke combustion kinetics and quantification of the different coke fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other authors have observed two differentiated coke morphologies by SEM and TEM microscopy: (i) an amorphous or encapsulating coke, pointed as the responsible for a higher deactivation, since it blocks the metallic sites, and (ii) a structured or filamentous coke, whose contribution to deactivation is hardly noticeable, unless a massive filaments growth takes place and the entrance of reactants through the catalyst pores is hampered . In a previous work, Ochoa et al . studied the nature and location of the total coke deposited on a Ni/La 2 O 3 ‐αAl 2 O 3 catalyst in the steam reforming of bio‐oil at different operating conditions, using SEM and TEM microscopy, TPO, and XPS, Raman and FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%